Simultaneously strengthening and toughening soy protein isolate-based films using poly(ethylene glycol)-block-polystyrene (PEG-b-PS) nanoparticles. Issue 86 (2nd September 2016) - Kang, Haijiao; Shen, Xiaoyan; Zhang, Wei; Qi, Chusheng; Zhang, Shifeng; Li, Jianzhang
Abstract : Uniformly dispersed PEG- b -PS nanoparticles synthesized via RAFT dispersion polymerization was employed to reinforce the biodegradable soy protein isolate films. Abstract : Well-defined, vesicle-like nanoparticles of poly(ethylene glycol)- block -polystyrene (PEG- b -PS) diblock copolymers, synthesized via a macro-RAFT agent of PEG45 -TTC (where "TTC" is the RAFT terminal of trithiocarbonate) mediated dispersion polymerization of styrene, were used to prepare enhanced SPI-based nanocomposite films in this study. The uniform dispersion of the PEG45 - b -PS276 nanoparticles into the SPI matrix was confirmed by transmission electron microscopy and field emission scanning electron microscopy. The simultaneously strengthening and toughening mechanism of the SPI-based nanocomposite films was achieved. This was accomplished by discontinuous filling of nanoparticles into the SPI matrix due to the hydrophobic PS core which served as the hard-domains to strengthen the mechanical properties of the resultant films. Concurrently, the hydrophilic PEG block was conjunct with the SPI chains through hydrogen bonding, increasing the compatibility between nanoparticles and the SPI matrix, ultimately transferring interfacial stress and increasing the elongation of the resulting films. Compared to unmodified SPI film, the tensile strength and elongation at break value of the SPI/PEG- b -PS nanocomposite films were improved by 85.3% and 11.5%, respectively. Further, the total soluble matter of the nanocomposite films was reduced by 59.7% compared to the control. The surface hydrophobicity of the films was also elevated due to the hydrophobic PS core surface-aggregation. The diblock copolymer examined here, as opposed to other nanofillers, may be the first to be successfully introduced into the SPI biopolymer matrix to fabricate high-performance bio-nanocomposite films.